PKM Pelatihan Pembuatan Lembar Kerja Fisika Berbasis Culturally Responsive Teaching (CRT) Sebagai Pendukung Kurikulum Merdeka di SMA Negeri 5 Takalar - Hasyim, Mutahharah; Martawijaya, M. A.; Usman, Usman; Taqwin, Muhammad (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
The preparation of human resources (HR) with 21st-century skills has become a priority for the government through the implementation of the independent curriculum at the secondary school level. This curriculum adopts the 6Cs (Critical Thinking, Collaboration, Creative Thinking, Character Education, Citizenship, and Communication) values to realize intelligent, critical, and creative students. One of the learning approaches used is Culturally Responsive Teaching (CRT), which emphasizes cultural inclusivity in learning. At SMA Negeri 5 Takalar, although learning is active, there are still areas for improvement in practicum activities requiring Student Worksheets (SW). To overcome this, the proposer team held training on preparing CRT-based SW, which integrates local wisdom into the curriculum. This training aims to improve teachers' competence in compiling SW by the Independent Curriculum and support the implementation of practical practicum and student character development. The activity results showed an increase in teachers' knowledge and skills in compiling CRT-based SW, which impacted the quality of learning in the school.